The Double Rider : a Western Story - Brand, Max, 1892-1944 (Five Star, A part of Gale, Cengage Learning, 2013)
Hired to impersonate a man who wants to know why he has been summoned to the family home of a person he was accused of killing years earlier, Ned Rippon befriends a family member and struggles to discover whether his targets or his employer are trustworthy.